2021
DOI: 10.1111/1346-8138.15955
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for DOCK8 deficiency‐related severe dermatitis

Abstract: Dedicator of cytokinesis 8 (DOCK 8) gene immunodeficiency syndrome is a progressive combined immunodeficiency characterized by a combined defect in humoral and cellular immunity. First described in 2009 1,2 , it is caused by biallelic mutations in DOCK8, encoding a guanine nucleotide exchange factor highly expressed in lymphocytes that regulate the actin cytoskeleton. 3 In the past, it was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…In a pooled analysis of clinical trials, the overall infection risk was not increased in patients under dupilumab compared to the placebo group 69 . Furthermore, in our study, a reduced infection risk had also been reported in two patients with HIES, which may be related to a restoration of balance between Th1 and Th2 immunity 25,30 . Based on the current literature, the use of dupilumab is generally safe in patients with genodermatosis.…”
Section: Discussionsupporting
confidence: 69%
“…In a pooled analysis of clinical trials, the overall infection risk was not increased in patients under dupilumab compared to the placebo group 69 . Furthermore, in our study, a reduced infection risk had also been reported in two patients with HIES, which may be related to a restoration of balance between Th1 and Th2 immunity 25,30 . Based on the current literature, the use of dupilumab is generally safe in patients with genodermatosis.…”
Section: Discussionsupporting
confidence: 69%
“…240 It may also improve AD related to IL4/4R, IL13, DOCK8, CARD11, STAT3, SPINK5, ERBB2IP, and ZNF341 dysregulation. [241][242][243][244][245][246][247][248] Tralokinumab targets IL13 and is approved for moderate to severe AD in adults. 77 Topical ruxolitinib and oral upadacitinib, abrocitinib, and baricitinib (approved in Europe and Japan) are JAK inhibitors indicated for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also support dupilumab treatment of atopic dermatitis in non- STAT3 -related-IEI, such as DOCK8 deficiency ( 40 ), CARD11-associated atopy with dominant interference of NF-kB signaling (CADINS) ( 41 ), Wiskott-Aldrich Syndrome ( 42 ), common variable immune deficiency (CVID) ( 43 ), TTC7A-associated combined immunodeficiency ( 44 ), and X-linked agammaglobulinemia ( 45 47 ). Thus, indications for dupilumab use in IEI are rapidly expanding, and it should be considered a main therapeutic modality in adult patients with AD-HIES along with standard topical care.…”
Section: Discussionmentioning
confidence: 77%